2021
DOI: 10.1111/jth.15170
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenic hotspots in the spacer domain of ADAMTS13 in immune‐mediated thrombotic thrombocytopenic purpura

Abstract: Background Immune‐mediated thrombotic thrombocytopenic purpura (iTTP) is caused by anti‐ADAMTS13 autoantibodies inducing a severe deficiency of ADAMTS13. Epitope mapping studies on samples obtained during acute iTTP episodes have shown that the iTTP immune response is polyclonal, with almost all patients having autoantibodies targeting the spacer domain of ADAMTS13. Objectives To identify the immunogenic hotspots in the spacer domain of ADAMTS13. Patients/methods A library of 11 full‐length ADAMTS13 spacer hyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…These data showed that the majority of the samples without anti-CS autoantibodies also did not have detectable anti-S autoantibodies when screening the samples on the ADAMTS13 variant where the spacer domain was swapped for the ADAMTS1 spacer domain. 32 The differences between our study and the majority of the epitope mapping studies might be due to the different types of assays used because we demonstrated direct binding of anti-CS autoantibodies to the coated CS fragment, whereas in the previous 2 largest epitope-mapping studies, the presence of anti-CS autoantibodies was deduced from data of autoantibodies binding to MDTCS fragments (ie, negative for binding to MDT 11 or MD/MDTC 6 and positive for binding to MDTCS). Whether differences in the percentage of patients with iTTP with detectable anti-CS autoantibodies in the different studies could be related to diverse ethnicity could not be investigated because information on ethnicity was not available for our patient cohort.…”
Section: Discussionmentioning
confidence: 99%
“…These data showed that the majority of the samples without anti-CS autoantibodies also did not have detectable anti-S autoantibodies when screening the samples on the ADAMTS13 variant where the spacer domain was swapped for the ADAMTS1 spacer domain. 32 The differences between our study and the majority of the epitope mapping studies might be due to the different types of assays used because we demonstrated direct binding of anti-CS autoantibodies to the coated CS fragment, whereas in the previous 2 largest epitope-mapping studies, the presence of anti-CS autoantibodies was deduced from data of autoantibodies binding to MDTCS fragments (ie, negative for binding to MDT 11 or MD/MDTC 6 and positive for binding to MDTCS). Whether differences in the percentage of patients with iTTP with detectable anti-CS autoantibodies in the different studies could be related to diverse ethnicity could not be investigated because information on ethnicity was not available for our patient cohort.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth highlighting that the majority of the anti-aggrecanase mAbs reported so far either block access of substrates to the active-site cleft, for example by “freezing” their target protease in a closed conformation (GSK2394002) or by binding to exosites in the Dis domain (2D3) . Alternatively, mAbs can block exosites in distal ancillary domains (2B9); the modality of action of these mAbs resembles those of autoantibodies against ADAMTS13 that mainly target the Sp domain . Unfortunately, exosite inhibitors have not yet fulfilled their mission.…”
Section: Discussionmentioning
confidence: 99%
“… 27 Alternatively, mAbs can block exosites in distal ancillary domains (2B9); 27 the modality of action of these mAbs resembles those of autoantibodies against ADAMTS13 that mainly target the Sp domain. 161 Unfortunately, exosite inhibitors have not yet fulfilled their mission. The fact that the anti-Sp mAb 2B9 inhibits not only the aggrecanase, but also the versicanase activity of ADAMTS5 22 may be a potential red flag for those who hope that these molecules may be able to achieve substrate-specific inhibition, even if such an effect is desirable from a therapeutic point of view.…”
Section: Discussionmentioning
confidence: 99%
“… 40 Epitope mapping studies of immune‐mediated TTP (iTTP) patients' autoantibodies have progressively revealed that in the majority of patients the spacer domain of ADAMTS13 is targeted by autoantibodies. 41 , 42 , 43 Several domains of ADAMTS13 may be targeted simultaneously in almost any combination 44 , 45 , 46 , 47 ; nonetheless, anti‐spacer antibodies, when present, normally constitute the main bulk of the autoantibodies' mixtures in iTTP patients. 45 , 47 , 48 , 49 The long‐term description of patients' outcome following the acute phase, leading to consider TTP as a chronic relapsing disease.…”
Section: A Brief History Of Thrombotic Thrombocytopenic Purpura ( ...mentioning
confidence: 99%